Impact of the surgical modality for axillary lymph node dissection on postoperative drainage and seroma formation after total mastectomy - Isozaki, Hiroshi (Patient Saf Surg, 2019)
BACKGROUND: The most common complications after total mastectomy with axillary lymph node treatment are prolonged drainage and seroma formation. The aim of this study was to find factors correlated with prolonged fluid discharge (prolonged drainage or seroma formation after 20th operative day or later), including surgical techniques or devices and clinical factors. PATIENTS AND METHODS: A total of 202 conclusive primary breast cancer patients underwent total mastectomy with axillary lymph node treatment between January 7, 2014 and June 20, 2018 at our hospital. The factors that correlated with the total fluid discharge volume and prolonged fluid discharge were examined statistically. The surgical modalities for total mastectomy with axillary treatment were classified into the following three groups:, Group A; skin flap formation by EC and axillary lymph node dissection by EC with ligation of the arteries and veins, Group B; skin flap formation by EC and axillary lymph node dissection by ultrasonic dissector (UD) without ligation of the vessels. Group D; skin flap formation by electrocautery (EC) and axillary lymph node dissection by picking up using forceps and ligation (PL). RESULTS: The total fluid discharge volume and prolonged fluid discharge after total mastectomy with sentinel node retrieval (33 patients) were significantly lower than those after total mastectomy with axillary lymph node dissection (169 patients). In patients treated without drainage, a high rate of seroma formation and prolonged fluid discharge were observed, and 1 patient developed seroma infection. In the total mastectomy with axillary lymph node dissection group, logistic regression analysis revealed that body mass index, 1-week drainage volume, and surgical modality were independently correlated with prolonged fluid discharge. CONCLUSIONS: The surgical procedure for axillary lymph node dissection should be considered to avoid prolonged fluid discharge, and the lymph vessels should be ligated in axillary lymph node dissection. An ultrasonic dissector was not effective in reducing the total fluid discharge volume. An optimal axillary lymph node dissection technique should be developed. For the patients without drainage, careful postoperative treatment should be given to avoid infectious seroma formation, even for patients who underwent total mastectomy with sentinel lymph node retrieval.